A Guiding Hand or a Slap on the Wrist: Can Drug Courts be the Solution to Maternal Opioid Use? - O'Connor, Cara (2019)
As the opioid epidemic has expanded its reach, the number of pregnant women addicted to opioids has increased exponentially in recent years. The increase in the number of opioid-addicted pregnant women has resulted in a drastic expansion in the number of newborns who experience Neonatal Abstinence Syndrome (NAS). Newborns affected with NAS experience painful withdrawal and cost more to care for due to their increased health needs. In an effort to address the growing number of pregnant women using opioids and babies born with NAS, some states have turned to the criminal justice system. Three states–Tennessee, South Carolina, and Alabama–have criminalized maternal drug use, either through construction of a new statute or by using existing statutes for this purpose, which has been upheld in their courts. Although high courts in many other states have continuously determined that such prosecutions are unlawful, women across the United States continue to face criminal charges for their substance use while pregnant. This Comment addresses the concerns opioid addicted pregnant women pose to the criminal justice system and argues that drug courts are a crucial component to comprehensive reform. The drug court system needs to follow the lead of a recently established drug court in Buffalo, New York and embrace necessary reforms to better serve the health needs of pregnant women struggling with opioid addiction. This Comment argues the following reforms are necessary to effectively adjudicate cases involving pregnant drug use: expedited proceedings to begin treatment and avoid jailing; access to medication-assisted treatment; allowing women to spend time with their newborns; an appropriate sanctions system that recognizes the medical reality of relapse; and funding considerations that prevent women from having to pay for treatment. If drug courts are part of a comprehensive solution to treatment for opioid addiction, these reforms can contribute to better meeting the health care needs of women and their children